PENGARUH GAYA KEPEMIMPINAN DAN KOMPENSASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT AFI TOUR JAKARTA SELATAN - Alifia Rima Az’zahra; Feb Amni Hayati (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of leadership style and compensation on employee work productivity at PT AFI Tour South Jakarta. The population in this study were all employees of PT AFI Tour South Jakarta, while the sample was all employees of PT AFI Tour South Jakarta, namely 66 employees. The sampling technique was a saturated sampling technique. The analysis tool used in this study was multiple linear regression. The results of the study partially showed that leadership style had a significant effect on employee work productivity at PT AFI Tour South Jakarta, this was t-count> t-table or 6,415> 1,99834 and a significant value <0,05, while compensation had a significant effect on employee work productivity at PT AFI Tour South Jakarta, this was indicated by the value of t- count> t-table or 3,938> 1,99834 and a significant value <0,05. Simultaneously, leadership style and compensation have a significant effect on employee work productivity at PT AFI Tour South Jakarta, this is indicated by the Fcount value> Ftable or 22,062> 3,14 and a significant value <0,05. The R2 value of 0,287 indicates that employee work productivity is influenced by leadership style and compensation by 41,2% while the remaining 58,8% is influenced by other factors outside this study.